PSYCHOLOGICAL ASPECTS OF THE FAMILY INSTITUTION AND GENDER STEREOTYPES IN FORMING THE SOCIAL CONSCIOUSNESS OF YOUTH IN THE CONDITIONS OF INFORMATION ATTACKS. (Universal International Scientific Journal, 2026)
The article analyzes the influence of the family institution and gender stereotypes on the formation of social consciousness of young people in the conditions of information attacks. Various ideological and informational influences in the modern information space have a significant impact on the worldview and social consciousness of young people, therefore, the formation of their spiritual and moral immunity is an urgent issue. The article discusses the role of the family environment, the educational approach of parents and psychological relationships, as well as the influence of gender stereotypes on child upbringing and social consciousness. It is emphasized that strengthening the psychological environment of the family is an important factor in protecting young people from the negative impact of information.
Keywords: Information threats; youth social consciousness; family institute